A Spatial Estimation of Groundwater Recharge in Southern Ontario, Canada - Abdelhaleem Khader (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Efficient management of groundwater resources is needed, due to their importance and susceptibility to depletion and contamination. This requires better understanding and accurate quantification of groundwater recharge, which is the main source for replenishment of groundwater aq-uifers. Choosing a method for estimating recharge is largely dependent on the objectives of recharge estimation, spatial and temporal scales, availability of data, and the available resources in terms of time and ex-pense. The focus of this paper is estimating the spatial distribution of groundwater recharge for the objective of designing a groundwater moni-toring network. In this case, the ability to capture spatial variation of re-charge is the key attribute of the chosen method for estimating recharge. At the same time, the data needed for the method should be readily available so that the method can be applied in different regions that might differ in data availability. Precipitation-Runoff Modeling System (PRMS) has been utilized in this paper to estimate recharge in a study area in southern Ontario, Canada. The data on climate, geomorphology and geology needed to parameterize the model, and streamflow data needed to calibrate and validate the model were available online from federal and provincial agencies websites. Calibration and validation results show a good match between simulated and observed streamflow. An independent estimate of recharge was provided by a recession-curve displacement method, which uses only streamflow data. A comparison of the two methods shows a large difference in recharge estimates due to fundamental differences in recharge definition. PRMS results will be used in the groundwater monitoring network design because they are spatially distributed, and because PRMS conceptual model better represents the physical processes.